Response of Seven Woody Ornamentals to Turfgrass Herbicide Applications of Arylex, Penoxsulam, and Pyrimisulfan - J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2017)
Continued testing of turf-applied herbicides are being conducted to ensure off-target plant injury does not occur in the landscape. Results indicate high herbicide safety on select landscape ornamentals with new herbicides used to manage weeds in turf.
Keywords: ornamental herbicide tolerance; penoxsulam; pyrimisulfan